The Effects of Different Water Treatments on the Growth, and Health of Ornamental Fishes Raised under the Water Conditions - M, Navaneethan; S, Raja (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
In freshwater fish culture, water quality poses a serious hazard to survival and growth. To understand this high-risk factor associated with the poor water quality in the aquarium system, the hematological, histological, immunological, antioxidant, and growth performance of C. auratus, C. carpio, and P. hypophthalmus in the aquarium with different water treatment efficiencies and one without water filtration were compared. The experiment was conducted for approximately 120 days using water treatments: 1. PF, 2. BF, 3. PBF, 4. PBUVF, 5. WoF. Results showed that Fish health concerning turbidity (98%) was significantly reduced during post-filtration (PF, BF, PBF, and PB-UV-F) (p<0.05). In experimental tanks, water-treated fish showed improved growth and a 90% survival rate (p<0.05). In pot and bamboo filters, the hematological parameters such as RBC (93%, 94%, and 93%), WBC (79%, 18%, and 91%), and MCHC (93%, 45%, and 90%) were in the optimum levels during post filtration experiment. The immune response (IgM, C3, C4, NOS, and LSZ) of enzyme activities in the gut and liver of aquarium fishes and antioxidant parameters in the gut and liver (ABTS, CAT, GR, SOD, and LPO) were also the low-risk level where the water treatments in the aquarium tanks. In conclusion, our findings show that installing filtration systems in freshwater fish culture has helped to successfully regulate the fish health and water quality of aquariums and ensure their proper maintenance.